Mathematical Foundations of Cartography - Darina Stachova (Communications - Scientific letters of the University of Zilina, 2010)
The aim of this contribution is to acquaint the reader with a specific part of mathematical cartography that is interesting not only from the point of view of mathematics, but also from the point of view of constructive geometry.